Problems of Biology Education College Students in Journal Publication: Preliminary Analysis and Solutions - Hery Fajeriadi; Aminuddin Prahatama Putra; Dharmono Dharmono; Syahmani Syahmani; Muhammad Zaini; Riza Arisandi (Universitas Lambung Mangkurat, 2025)
The increase in the quantity of student publications in scientific journals has not been optimally followed by an improvement in their quality. Articles published in unaccredited journals still dominate compared to those published in nationally accredited journals. This study explores students' abilities and difficulties in publishing articles in journals. The method used is survey research. The population was lecturers and students of the Biology Education Study Program at Lambung Mangkurat University (ULM) Banjarmasin. The student categories targeted were those who had never published, were learning to publish, and had already published, with a total of 196 students. Ten lecturers and 49 students were selected as the sample using random sampling techniques. Data were collected through a Google Form questionnaire and analyzed descriptively. The results revealed that students face difficulties in publishing in journal articles due to a lack of understanding of journal article writing guidelines, the absence of clear and practical article writing guides, and suboptimal supervision from lecturers for students interested in writing for journal publication. The alternative solution offered from the data is to make guidelines for preparing articles for journal publication and provide assistance in writing articles intensely and periodically.